The Layton court mystery : a Roger Sheringham case - Berkeley, Anthony, 1893-1971 (House of Stratus, 2001)
Mr Victor Stanworth, an apparent carefree sixty-year-old, is entertaining a party of friends at his summer residence, Layton Court. When one morning he is found shot dead in the library it is hard to believe it is either suicide or murder. As one of the country-house guests gentleman sleuth Roger Sheringham resolves to solve the murder. As he pursues the truth he does not conceal any of the evidence, and the reader is able to follow his detection work to the conclusion of this original mystery story. AUTHBIO: A journalist as well as a novelist, Anthony Berkeley was a founding member of the Detection Club and one of crime fiction's greatest innovators. He was one of the first to predict the development of the 'psychological' crime novel and he sometimes wrote under the pseudonym of Francis Iles. He wrote twenty-four novels, ten of which feature his amateur detective, Roger Sheringham.